Pengembangan Kawasan Jagung Berbasis Korporasi Petani di Kabupaten Lebak, Banten - Ika Setiasih; nFN Suharno; Achmad Suryana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2020)
The main problem faced by small-scale farming is that the economy of scale cannot be reached so that the use of inputs and technology is inefficient. To overcome this problem, farmers need to join and cooperate in a farming group. One of the models of this cooperation is the agricultural area development based on farmer corporation that combines technical business aspects with farmer institutions aspects. This study aims to analyze the achievements of a pilot project implementation of the corn area development based on farmer corporation in Lebak Regency, Banten Province, which analyzed using the evaluation model of contect, input, process, product (CIPP) and determine priority strategies which analyzed using Analytical Hierarchy Process (AHP). The result of this study shows that the pilot project targets for the first and the second years, namely cooperation with the feed industry and forming its own feed processing, respectively have not been achieved. From the identified seven success indicators, three were achieved, namely production increase, income increase, and implementation of local specific innovative technology. The strategy that needed to be set in advance as a priority was farmer empowerment through a farmer institution, with the most important factor is farmers’ welfare achievement.